Boot camp - Strasser, Todd (Simon & Schuster Books for Young Readers, 2007)
After ignoring several warnings to stop dating his teacher, Garrett is sent to Lake Harmony, a boot camp that uses unorthodox and brutal methods to train students to obey their parents.